Smoking, F2RL3 methylation, and prognosis in stable coronary heart disease - Breitling, Lutz Philipp; Pfütze, Katrin; Burwinkel, Barbara; Brenner, Hermann (European heart journal, 2012)
Abstract: Aims: In a recent genome-wide study, cytosine bases in the F2RL3 gene, which codes for a protein relevant for cardiovascular physiology, were discovere
Online publish-ahead-of-print 17 April 2012
Gesehen am 26.06.2018